Content with Failure? Cultural Consolidation and the Absence of Nationalist Mobilization in the Case of the Occitans in France. Issue 2 (22nd May 2019) - Sasaki, Yu
Abstract : Does cultural consolidation among ethnic groups lead to nationalist mobilization? Extant research in the study of nationalism suggests a tight connection between the two. My article addresses this question by operationalizing cultural consolidation through language standardization and by providing an empirical analysis. I argue that not all ethnic groups that consolidate their culture build institutions toward sovereignty and propose that cases that fail to invest in institutions make strong contributions to the existing framework in the literature. Following a brief survey on the Bulgarians as a case of successful mobilization, I document evidence from an in-depth study on the Occitans, a minority ethnic group in France, as a failed case. Findings from a process-tracing approach indicate that although the Occitans standardized their language by 1900, their leading intellectuals grew content became content with the situation and failed to make the next move. I contribute by operationalizing cultural consolidation and by introducing "institution-building" as a crucial outcome between cultural consolidation and state-building. My article suggests that decisions of ethnic elites matter to understand why some groups start nationalist mobilization.